The forgotten (anti-Apartheid) "freedom fighters": Nigerian reggae music and cultural memory in a post-Apartheid era. Issue 1 (2nd January 2016) - Emielu, Austin
ABSTRACT: In the narratives of the role of music, musicians and literary artists in the Apartheid struggle, not much attention has been paid to contributions outside the South African Development Community (SADC). Yet, there were a large constituency of musicians and artists from Nigeria and the rest of Africa whose genres explored a range of thematic concerns that had Apartheid as a catalyst. These "freedom fighters" and their works seem to have been forgotten in a post-Apartheid era, suggesting some form of cultural amnesia. This paper attempts to fill this lacuna by bringing to fore the literary and artistic contributions of Nigerian musicians as a way to help post-Apartheid cultural memory to recuperate. The paper undertakes this through an examination of the repertoires, language use, lyrics, themes and iconographies in the works of these artists.